E-Assessment on Student's Self-Concept for Physics Learning - Astalini, Astalini; Darmaji, Darmaji; Kurniawan, Dwi Agus; Anggraini, Lika; Perdana, Rahmat (Jurnal Ilmu Pendidikan, 2019)
This study aims to apply students' self-concept E-assessment to SESKA-based physics. Student self-concept E-assessment in this study aims to see students 'self-concept of physics and how the teacher responds to the development of students' self-concept E-assessment with SESKA systems. The method implemented in this research has three stages, namely: (1) Development, (2) Implementation, & (Evaluation). This research was carried out on 450 students and 15 teachers in the Jambi Province of Indonesia. The results of this study indicate students' self-concept of physics is classified as good 47.1percent (212 students), and the teacher's response is classified as positive, with 66.7percent (10 teachers). Therefore, SESKA-based E-Assessments receives a good response and needs to be developed on a large scale.